The men who made the Constitution : lives of the delegates to the Constitutional Convention - Vile, John R. (The Scarecrow Press, Inc., 2013)
Few events in the history of the United States were of greater consequence than the Constitutional Convention of 1787. Although most histories have focused on the issues and compromises that dominated the debates, the exchanges were also shaped by the dynamic personalities of the fifty-five delegates who attended from twelve of the thirteen states. In The Men Who Made the Constitution, constitutional scholar John R. Vile explores the lives and contributions of all delegates to the 1787 Constitutional Convention, including those who left before the Convention ended and those who stayed until the last day but refused to sign. Each biography records the delegate's birth, education, previous positions or public service roles, homes, family life, life after the Convention, death, and resting place. Drawing directly from Convention debates and a vast array of secondary sources, Vile covers the positions of each delegate at the Convention on both major and minor issues and describes his service on committees and afterward at state ratification conventions. The Men Who Made the Constitution includes a bibliography of key sources, engravings of delegates for whom portraits were created, a quiz on key facts, and a transcript of the Constitution of the United States. This work is the perfect reference for students and scholars, as well as professional and amateur historians, of colonial and early American history, constitutional law, and American jurisprudence. -- Back cover.